PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA SMP - Abdul Wahid; Rukli Rukli; Nursakiah Nursakiah (Universitas Muhammadiyah Makassar, 2022)
The main problem in this study is whether there is a difference in the application of problem-based learning models and direct learning to mathematics learning outcomes in seventh grade students of UPT SMP Negeri 15 Selayar Islands. This study aims to determine the differences in the application of problem-based learning models and direct learning to mathematics learning outcomes in seventh grade students of UPT SMP Negeri 15 Selayar Islands. This type of research is an experimental study involving two classes, namely the experimental class and the control class. This research refers to the learning outcomes of mathematics. The design used in this study is a nonequivalent control group design. The research sample amounted to 64 students. The data analysis technique used is descriptive statistical analysis and inferential statistics using t-test.The results showed that after going through the application of the problem-based learning model, the results of the data analysis of students' mathematics learning outcomes were in the very good category, with an average score of 80% in the experimental class and the results of data analysis of students' mathematics learning outcomes were in the good category with an average score. an average of 70% in the control class. The results of the analysis with the t-test of the results of hypothesis testing using SPSS version 25 software obtained Sig , ie 0.000 0.05 so that H_0 is rejected and H_1 is accepted. This shows that there are differences in the application of problem-based learning models to students' mathematics learning outcomes. The results of observation of student activities 91% of students who actively participate in the mathematics learning process and 94% of students who give a positive response to the application of problem-based learning models (PBM), the implementation of mathematics learning with problem-based learning models with an average of 3.883% of the ideal score of 4, 0. From the results of this study, it can be concluded that there are differences in the application of problem-based learning models and direct learning to mathematics learning outcomes in class VII students of UPT SMP Negeri 15 Selayar Islands in learning mathematics.